2006
DOI: 10.1021/ol0621405
|View full text |Cite
|
Sign up to set email alerts
|

Rigid Linear and Star-Shaped π-Conjugated 2,2‘:6‘,2‘ ‘-Terpyridine Ligands with Blue Emission

Abstract: A series of rigid linear and star-shaped pi-conjugated 2,2':6',2"-terpyridine derivatives with the C-C single-, double-, and triple-bond linkages have been developed through the Suzuki, the Sonogashira, and the Wittig reactions. Such large rigid ligands exhibit strong blue emission in dilute solutions. [structure: see text]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(36 citation statements)
references
References 51 publications
(19 reference statements)
1
34
0
Order By: Relevance
“…394 nm belonging to the absorption band of the thienylterpyridinefunctionalized truxene groups. In comparison with the absorption spectra of other phenylterpyridine-functionalized truxenes (l max % 342 nm), [19] the low energy bands of the star-shaped 7 were red-shifted by 52 nm, indicative of enhanced conjugation through the thienyl spacer. Both ligands are fluorescent with the emission spectrum of 1 characterized by an intense emission band at 359 nm, a less intense band at higher energy (343 nm), and a lower energy shoulder shifted to the red at 376 nm.…”
Section: Resultsmentioning
confidence: 94%
“…394 nm belonging to the absorption band of the thienylterpyridinefunctionalized truxene groups. In comparison with the absorption spectra of other phenylterpyridine-functionalized truxenes (l max % 342 nm), [19] the low energy bands of the star-shaped 7 were red-shifted by 52 nm, indicative of enhanced conjugation through the thienyl spacer. Both ligands are fluorescent with the emission spectrum of 1 characterized by an intense emission band at 359 nm, a less intense band at higher energy (343 nm), and a lower energy shoulder shifted to the red at 376 nm.…”
Section: Resultsmentioning
confidence: 94%
“…Thus, subjecting the bromine-bearing azaindoles 1 n and 1 o to Suzuki coupling conditions with benzeneboronic acid gave the corresponding arylated azaindoles 1 p and 1 q in yields of 53 and 82 %, respectively (see Scheme 3). [14,15] Formation of pyrroles from one molecule of a silicon-tethered diyne and two molecules of the same organonitrile: It was previously found that iPrCN, a relatively bulky organonitrile, could stop the above reaction involving two molecules of organonitriles midway to give multisubstituted pyrroles upon hydrolysis of the reaction mixtures. [9] Inspired by this finding, we searched for a variety of organonitriles with appropriate steric hindrance to stop the reaction midway and efficiently prepare substituted pyrroles 3.…”
Section: Resultsmentioning
confidence: 99%
“…Compounds 2, 7, 14-18, T14 and T15 were prepared following previously published protocols. [17,27,43] All the terpyridine derivatives were purified by flash column chromatography (neutral alumina, CH 2 Cl 2 /MeOH as eluent) or preparative size-exclusion chromatography (BioBeads ® S-X5, toluene as eluent). The commercially available boronic acids 5 and 6 were converted into the corresponding ethylene glycol boronate by heating with ethylene glycol at reflux in toluene.…”
Section: Methodsmentioning
confidence: 99%
“…The general reaction scheme for the synthesis of the bis(terpyridines) T8-T16 by linking functionalized 4Ј-phenyl-2,2Ј:6Ј,2ЈЈ-terpyridines 17 and 18 to the spacer units 8-16 is shown in Figure 1. By using halogen end-groups, the systems were coupled to a terpyridine derivative bearing an ethynyl functionality (17) by Sonogashira reaction to yield the conjugated bis(terpyridines) T10, T11 and T15. The Huisgen 1,3-dipolar cycloaddition reaction [33] under Cu I catalysis, one of the socalled "click" reactions, [34][35][36][37][38] was used to connect the terpyridine and the spacer in the cases of compounds T12, T13 and T16.…”
Section: Synthesis Of Bis(terpyridines)mentioning
confidence: 99%
See 1 more Smart Citation